Covid-19 and contact lenses: Practice re-entry considerations. Issue 8 (August 2020) - Jones, Lyndon; Walsh, Karen
Abstract : fessor Lyndon Jones and Karen Walsh consider safe contact lens practice as clinics move out of lock-down (C 76118, one distance learning CET point suitable for optometrists, dispensing opticians, contact lens opticians and therapeutic optometrists)